Plastic surgery of defects in the bones of the cranial vault with a carbon implant - Mirzayuldashev N.Yu; Isakov B.M; Tashlanov F.N; Isakov K.B; Madaminzhonov U.O (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The analysis of the results of surgical treatment of 67 patients with defects of the bones of the cranial vault previously operated for traumatic brain injury. Indications for surgical treatment are indicated depending on the size of the bone defect. Carbon composite material was used as a bone-plastic material. In most cases, a good result was obtained - 86.5%.